ICE MAKER QUALITY SYSTEM ANALYSIS - Naufal Afif Zuren Fauzan (Jurusan Pendidikan Teknologi Dan Kejuruan, 2022)
Ice Maker is a tool used to make ice cubes quickly and automatically. For this reason, research was carried out on ice cubes produced by ice makers to determine which ice cubes met consumer criteria, the purpose of this study was to analyze consumer responses so that a cube could meet the criteria that consumers wanted. This study uses the MMR (Mixed Method Research) research method and data collection for 10 respondents from beverage outlets in Palangka Raya, the data taken is in the form of a questionnaire on the value of each indicator that affects the criteria for ice cubes. The results showed that the first indicator, namely the maturity level of ice cubes, had an average of 12.90, giving an idea that the maturity level of ice cubes had reached a satisfied value. The second indicator, namely the taste of ice cubes, has an average value of 12.70, giving an idea of ​​the taste of ice cubes using the ice maker has reached a satisfied value.